Students of Chinese learning strategies on online class - Chao Chao, Kuok Wa (2024)
This research analyzes the results of the learning strategies of Costa Rican students in Chinese online from 2020 to 2022. This research is located within the positivist paradigm with a quantitative approach, its results are presented in a statistical and percentage way, under a simple random probability sampling. It investigates the strategies used by the students on the learning of phonetics, morphosyntax, lexicon, Chinese character writing  and cultural elements from the methodologies for learning Chinese and also the use of direct strategies, namely: memorization, cognitive and compensatory strategies and indirect strategies such as metacognitive, affective and social strategies. It was found that there is a high predilection on the part of the students to carry out all the activities with the help of some technological tool, but combining it with traditional language learning strategies such as constant repetition of words, writing the word several times, making sentences. As an innovative element we can mention the creation of mental maps that allows participants to reflect on the functioning of Mandarin, besides this is a high-level cognitive process that allows them to create relationships between concepts and gives them a very important mental plasticity for learning a language as complex as Chinese from the point of view of phonetics and calligraphy to mention the most significant.